1999
DOI: 10.1016/s0304-3959(99)00119-0
|View full text |Cite
|
Sign up to set email alerts
|

The kappa opioid nalbuphine produces gender- and dose-dependent analgesia and antianalgesia in patients with postoperative pain

Abstract: Nalbuphine, pentazocine, and butorphanol, mixed agonist/antagonist opioids that induce analgesia by acting predominantly at kappa opioid receptors, have recently been shown in single-dose studies to have greater analgesic efficacy in women than in men. In the current experiments, the first placebo controlled dose response study of opioid analgesic efficacy that examines for gender differences, nalbuphine (5, 10, or 20 mg) and placebo were evaluated in 62 men and 69 women for the treatment of moderate to severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
151
3
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(166 citation statements)
references
References 24 publications
10
151
3
2
Order By: Relevance
“…42). Gear and colleagues (10)(11)(12)(13), in contrast, have reported that women are more sensitive to the inhibition of molar extraction pain by a number of nonselective -opioid analgesics including pentazocine. We observed a trend in the opposite direction presently: toward greater analgesia in nonredheaded men than women.…”
Section: Discussionmentioning
confidence: 98%
“…42). Gear and colleagues (10)(11)(12)(13), in contrast, have reported that women are more sensitive to the inhibition of molar extraction pain by a number of nonselective -opioid analgesics including pentazocine. We observed a trend in the opposite direction presently: toward greater analgesia in nonredheaded men than women.…”
Section: Discussionmentioning
confidence: 98%
“…For example, there is little mechanistic understanding of why women are more likely than men to experience myriad chronic pain syndromes (1-3) as well as recurrent pain, more severe levels of pain, and pain of longer duration (10). Similarly, reports of more robust κ-opioid receptor (KOR) antinociception in females vs. males (11)(12)(13)(14) are not accompanied by compelling mechanistic rationales.In addition to proposed genetic contributions (15), the milieu of ovarian sex steroids is thought to contribute to sex-dependent nociception (5, 6) and opioid antinociception (5, 16). However, sex steroid molecular targets and their altered functionality that are relevant to sex-dependent nociception and opioid antinociception are not defined.…”
mentioning
confidence: 99%
“…For example, there is little mechanistic understanding of why women are more likely than men to experience myriad chronic pain syndromes (1-3) as well as recurrent pain, more severe levels of pain, and pain of longer duration (10). Similarly, reports of more robust κ-opioid receptor (KOR) antinociception in females vs. males (11)(12)(13)(14) are not accompanied by compelling mechanistic rationales.…”
mentioning
confidence: 99%
“…However, prolonged use of morphine may lead to tolerance and, subsequently, withdrawal symptoms (Fernández-Dueñ as et al, 2007;Ledeboer et al, 2007;Noble and Roques, 2007). In trauma, rat model compounds, such as butorphanol, nalbuphine, meperidine, pentazocine, and codeine, can be used to alleviate acute pain, but buprenorphine is the analgesic recommended by veterinarians due to its potency and long-lasting duration (Kaiko et al, 1983;Gear et al, 1999;Katzung, 2001;Roughan and Flecknell, 2002). Moreover, subcutaneously administration of 0.05 mg=kg reduces pain sensitivity after postoperative surgeries (Curtin et al, 2009).…”
mentioning
confidence: 99%